The Impact of Human Resource Management (HRM) and Talent Management in Improving Employee Performance in Footwear Manufacturing Companies - Hermawati, Lusi; Agustian, Wahid Rahmat; Mawarida, Apriliani; Goestjahjanti, Francisca Sestri; winanti, winanti; Hasna, Shoftwatun; Farhan, Akhmad; Mendrofa, Yeremia; Singgih, Eman; Kumoro, Dwi Ferdiyatmoko Cahya (Journal of E-business and Management Science, 2024)
There are still many companies that do not understand the impact of Human Resource Management and Talent Management on employee performance in a Footwear Manufacturing Company. Globalization and increasingly tight business competition require manufacturing companies to manage Human Resources and talents effectively in order to achieve efficiency, innovation, and competitive advantage. So researchers are interested in conducting research with the title of the impact of human resource management (HRM) and talent management in improving employee performance in footwear manufacturing companies. With the research variables to be analyzed Human Resource Management X1, Talent Management X2, on Employee Performance as dependent variables. The results of the study can be seen from the multiple correlation level value obtained of 0.785, indicating that the correlation level obtained has a strong influence. The coefficient of determination value in this study is 0.616, meaning that Human Resource Management X1, Talent Management X2, on Employee Performance in footwear manufacturing has an influence of 61.6% and while the remaining 38.4% is influenced by other variables not included in this study. Meanwhile, the results of the F test, namely the simultaneous hypothesis, show a significant influence because F count > F table (462.498 > 3.280)